Total Productive Maintenance (Tpm) And Socio· Technical Aspects From Malaysian Manufacturing Industries Perspective - Mohd Shalahim, Nurul Shahida (2006)

(untitled)
Penyelenggaraan adalah suatu fungsi penting dalam sesebuah kilang pembuatan. Kilang pembuatan kini terdedah dengan perubahan paradigma yang baru dan pantas. Strategi penyelenggaraan seperti Penyelenggaraan Produktif Menyeluruh (TPM) harus diberi perhatian yang sewajamya oleh industri pembuatan. Selain dari itu, aspek sosioteknikal juga memainkan peranan penting di dalam sesebuah organisasi. Merujuk kepada perkara di atas, kajian ini menyelidik hubungan di antara dua praktis TPM iaitu Penyelenggaraan Autonomi (AM) dan Penyelenggaraan Terancang (PM) dengan sepuluh aspek sosio-teknikal iaitu: [1] keyakinan; [2] daya kepimpinan; [3] komunikasi; [4] motivasi; [5] kerja berpasukan; [6] sikap; [7] latihan; [8] pemberian kuasa; [9] kepunyaan; dan [10] pengkayaan tugasan. Maintenance is a vital function in manufacturing industries. Manufacturing industries are exposed to newer and rapidly changing paradigms. A well-conceived maintenance strategy such as Total Productive Maintenance (TPM) should deserve more attention by the manufacturing plants. Apart form that, the socio-technical aspects also playas an important role in the organisations. Referring to the above matter, this study investigates the interrelatedness between two TPM practises; Autonomous Maintenance (AM) and Planned Maintenance (PM) with ten socio-technical aspects which are: [1) confidence; [2) leadership; [3) communication; [4] motivation; [51 teamwork; [6) attitudes; [7] training; [81 empowerment; [91 ownership; and [10) job enrichment.